Comparison of spatial and non-verbal reasoning abilities in veterinarians in the fields of radiology and surgery - Gutierrez, Juan Claudio; Holladay, Steven D. (Frontiers in Veterinary Science, 2024)
Spatial ability tests measure capacity for mentally understanding and interpreting three-dimensional images. Such skills have been found to be predictive for anatomical learning success and proficiency in human and veterinary medical students. Veterinarians in the radiology and surgery field develop high levels of three-dimensional topographic anatomic understanding through exposure to anatomy portions of the veterinary curriculum, followed by highly specialized residency programs. Validated testing tools were used to compare spatial and general non-verbal reasoning abilities in veterinarians in the field of radiology (radiology group, RG) and veterinarians in the field of surgery (surgery group, SG). These tests were: Guay’s Visualization of Views Test: Adapted Version (GVVT), the Mental Rotation Test (MRT), and Raven’s Advanced Progressive Matrices Test, short form (APMT). Results showed a significant difference for GVVT scores in favor of the RG (15.2 ± 0.3 and 12.3 ± 0.4, respectively, p < 0.05). There were no significant differences in scores for MRT and APMT between the RG and SG. There was a significant positive correlation between spatial ability tests scores and general non-verbal reasoning test scores for the RG but not for the SG. Future studies are planned to determine if the RG innately possess high spatial and reasoning skills, and to expand the present findings to other veterinary specialty areas.